The genome of the Paleogene relic tree Bretschneidera sinensis: insights into trade-offs in gene family evolution, demographic history, and adaptive SNPs. (4th February 2022) - Liu, Hai-Lin; Harris, A J; Wang, Zheng-Feng; Chen, Hong-Feng; Li, Zhi-An; Wei, Xiao
Abstract: Among relic species, genomic information may provide the key to inferring their long-term survival. Therefore, in this study, we investigated the genome of the Paleogene relic tree species, Bretschneidera sinensis, which is a rare endemic species within southeastern Asia. Specifically, we assembled a high-quality genome for B. sinensis using PacBio high-fidelity and high-throughput chromosome conformation capture reads and annotated it with long and short RNA sequencing reads. Using the genome, we then detected a trade-off between active and passive disease defences among the gene families. Gene families involved in salicylic acid and MAPK signalling pathways expanded as active defence mechanisms against disease, but families involved in terpene synthase activity as passive defences contracted. When inferring the long evolutionary history of B. sinensis, we detected population declines corresponding to historical climate change around the Eocene–Oligocene transition and to climatic fluctuations in the Quaternary. Additionally, based on this genome, we identified 388 single nucleotide polymorphisms (SNPs) that were likely under selection, and showed diverse functions in growth and stress responses. Among them, we further found 41 climate-associated SNPs. The genome of B. sinensis and the SNP dataset will be important resources for understanding extinction/diversification processes using comparative genomics in different lineages.